Análisis del proceso de producción de la empresa tierra linda del cantón Píllaro provincia de Tungurahua en el periodo del 01 de enero al 31 de diciembre del 2011 - Saquinga Chicaiza, Alicia Maribel (2013)
The race it Administrative Sciences and Humanities, for its institutional life, has been training professionals with the skills to cope in the workplace and thus contributes to the development of society. Thus we conclude that one way to help his greatness, is the analysis of the production process of the company Tierra Linda. Since the purpose of the research is to highlight strengths, weaknesses, threats and identify opportunities to help improve the quality of the product that the industry provides to all its customers both domestic and foreign, in turn provides a good working environment for everyone involved, in the same way helps enlarge the company and therefore the community. In the present investigation has met the needs of the company with regard to product quality and supply and meet the objectives and targets set in the short, medium or long term and compliance activities. So we conducted a detailed analysis of the production process to determine the quality of the product that the company offers to its customers and the process followed to prepare the same maintaining its quality as well as price.